Magnetic micro-crack textile composite sensor and preparation method thereof

By coating a magnetic layer onto a textile substrate and forming a mesh-like microcrack, combined with liquid metal embroidery and a moisture-permeable encapsulation film, the problem of poor compatibility between traditional magnetic crack sensors and textiles is solved, realizing a magnetic microcrack textile composite sensor with high sensitivity, good breathability, and water resistance, suitable for wearable devices.

CN122237648APending Publication Date: 2026-06-19GUANGDONG VOCATIONAL & TECHNICAL COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610580377.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-29
Publication Date
2026-06-19

AI Technical Summary

Technical Problem

Traditional magnetic crack sensors are incompatible with textiles, cannot withstand repeated bending and washing, have poor air permeability, and are difficult to mass-produce due to their complex manufacturing process.

Method used

Using a textile substrate as a support layer, a mesh-like microcrack is formed by coating a magnetic coating and pre-stretching and drying. This is combined with liquid metal embroidery or conductive yarn weaving to form an induction coil, which is then encapsulated with a moisture-permeable and waterproof encapsulation film. The preparation method is compatible with textile equipment.

Benefits of technology

It achieves high-sensitivity bending detection, has good water-washing stability, excellent breathability, is suitable for wearable devices, and has good mass production feasibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122237648A_ABST
    Figure CN122237648A_ABST
Patent Text Reader

Abstract

This invention discloses a magnetic microcracked textile composite sensor and its preparation method, belonging to the field of intelligent textile technology. The sensor includes a textile substrate layer, a magnetic coating, an induction coil layer, and a moisture-permeable and waterproof encapsulation film. The magnetic coating is applied to the textile substrate layer and contains a mesh-like microcrack pattern. The induction coil layer is disposed on the magnetic coating and is formed by liquid metal embroidery or conductive yarn weaving. The moisture-permeable and waterproof encapsulation film covers the induction coil layer. This invention forms a mesh-like microcrack pattern in the magnetic coating through a pre-stretching-drying process, uses liquid metal embroidery or conductive yarn weaving to form the induction coil, and encapsulates it with a moisture-permeable and waterproof encapsulation film. The resulting sensor has good bending sensitivity, water washing stability, and breathability, meeting the sensing requirements of wearable devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of intelligent textile technology, specifically relating to a magnetic microcrack textile composite sensor and its preparation method. Background Technology

[0002] Wearable smart sensing materials, as an important branch of smart materials, have enormous application potential in fields such as human body sensing, artificial intelligence, and medical bionics. They will provide endless possibilities for human motion monitoring and health detection, attracting widespread attention from the academic community both domestically and internationally. Smart wearable fabrics are characterized by being lightweight, low-modulus, highly flexible and elastic, having diverse and multidimensional structures, low cost, and high skin-friendliness. Compared to sensing devices such as smart bracelets, smart glasses, and smart skin, they demonstrate unique advantages in the field of smart wearables.

[0003] Magnetic crack sensors, as an important type of flexible sensor, achieve their sensing function by detecting crack changes generated in magnetic materials during deformation. However, traditional magnetic crack sensors use brittle ferrite films as the sensing material, which cannot withstand repeated bending and washing of textiles. At the same time, the coil and magnetic layer are fixed by adhesive lamination, resulting in poor air permeability and stiffness in the textiles, and there is a risk of interface delamination. In addition, the crack structure depends on mechanical pre-stretching to generate, making it difficult to be compatible with fabric forming processes.

[0004] Chinese invention patent CN117128848A discloses a magnetic sensor that uses an adhesive layer to fix a ferromagnetic thin film and a coil. This structure has the risk of interface delamination during repeated bending, affecting the long-term stability of the sensor. A Nature paper (s41467-025-61784-0) discloses a ferrite thin film crack sensor that generates cracks through cylindrical rolling. However, this method cannot be directly applied to textiles, and the process is complex and difficult to scale up.

[0005] Therefore, developing a magnetic microcrack textile composite sensor that is compatible with textile processes and has good flexibility, breathability, and washability, as well as its preparation method, is of great significance for promoting the development of smart wearable devices. Summary of the Invention

[0006] This invention addresses the problems existing in the prior art by providing a magnetic microcrack textile composite sensor and its preparation method. The sensor uses a textile substrate as a support layer, forms a mesh-like microcrack by coating with a magnetic coating and using a pre-stretching-drying process, forms an induction coil by liquid metal embroidery or conductive yarn weaving, and encapsulates it with a moisture-permeable and waterproof encapsulation film. The resulting sensor has good bending sensitivity, water washing stability and breathability, and can meet the sensing requirements of wearable devices.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: First, this invention provides a magnetic microcrack textile composite sensor, comprising: Textile substrate layer; A magnetic coating is applied to the textile substrate layer. The magnetic coating comprises ferrite nanoparticles and waterborne polyurethane, and the magnetic coating has a network of microcracks. An induction coil layer is disposed on the magnetic coating layer, and the induction coil layer is formed by liquid metal embroidery or by conductive yarn weaving; A moisture-permeable and waterproof encapsulation film is provided, which covers the induction coil layer.

[0008] Preferably, the textile substrate layer is a polyester knitted fabric or a nonwoven fabric, and the ferrite nanoparticles are manganese-zinc ferrite nanoparticles.

[0009] Preferably, the thickness of the magnetic coating is 50μm-300μm, and the density of the mesh microcracks is 50-120 cracks / cm.

[0010] Preferably, the liquid metal is a gallium indium tin alloy, the conductive yarn is silver-plated nylon yarn, and the induction coil layer is a spiral coil or a planar inductor coil.

[0011] Preferably, the moisture-permeable and waterproof encapsulation film is an expanded polytetrafluoroethylene microporous film or a polyurethane microporous film, and the thickness of the moisture-permeable and waterproof encapsulation film is not greater than 20 μm.

[0012] Then, the present invention provides a method for preparing a magnetic microcrack textile composite sensor, comprising the following steps: Ferrite nanoparticles are mixed with an aqueous polyurethane dispersion to form a magnetic slurry, which is then coated onto a textile substrate layer to form a wet film. The textile substrate layer coated with a wet film is stretched under tension and then dried under heating conditions to form a network of microcracks on the surface of the magnetic coating. An induction coil layer is formed on the surface of the magnetic coating by liquid metal embroidery or conductive yarn weaving; A moisture-permeable and waterproof encapsulation film is applied to the induction coil layer, and then encapsulated using a hot-pressing process to obtain a magnetic microcrack textile composite sensor.

[0013] Preferably, the ferrite nanoparticles account for 60% of the mass of the magnetic slurry, and the thickness of the wet film is 150μm-250μm.

[0014] Preferably, the tension is 10N-20N, the heating temperature is 100℃-150℃, and the drying time is 8min-15min.

[0015] Preferably, the liquid metal embroidery is performed using a digital embroidery machine with the following embroidery parameters: needle speed 800 rpm, bobbin tension 3 cN, number of coil turns 6, line width 0.3 mm, and spacing 0.5 mm; the hot pressing process conditions are: temperature 120℃-140℃, pressure 0.4 MPa-0.6 MPa, and time 20 s-40 s.

[0016] Finally, this invention provides applications of the above-mentioned magnetic microcrack textile composite sensor in motion monitoring, posture recognition, or human-computer interaction.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The magnetic microcrack textile composite sensor of the present invention uses a textile substrate as a support layer. A mesh microcrack is formed by coating a magnetic coating and using a pre-stretching-drying process. The mesh microcrack deforms when the sensor is bent, causing a change in magnetic permeability, thereby achieving high-sensitivity bending detection with a bending sensitivity of up to 0.01°.

[0018] 2. The magnetic microcrack textile composite sensor of the present invention uses liquid metal embroidery or conductive yarn weaving to form an induction coil. The liquid metal has good conductivity and flexibility and can withstand repeated bending of textiles. The conductive yarn weaving process is compatible with textile processes, which is conducive to large-scale production.

[0019] 3. The magnetic microcrack textile composite sensor of the present invention is encapsulated with a moisture-permeable and waterproof encapsulation film. The moisture-permeable and waterproof encapsulation film has good waterproof and moisture-permeable performance, with a moisture permeability greater than 2000g / m² / 24h, ensuring the wearability of the sensor. At the same time, the encapsulation film can effectively protect the internal structure, giving the sensor good water washing stability, with the crack density change being less than 8% after 100 washing machine washes.

[0020] 4. The preparation method of the present invention adopts processes such as coating, pre-stretching-drying, embroidery or weaving, and hot-pressing packaging. All of these processes are compatible with existing textile equipment, can realize roll-to-roll production, and have a production speed of not less than 5m / min, thus having good feasibility for mass production. Attached Figure Description

[0021] Figure 1 This is an exploded view of the structure of the magnetic microcrack textile composite sensor of the present invention; Figure 2 This is a flowchart of the process for generating network microcracks according to the present invention. Detailed Implementation

[0022] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the invention in any way. The following content is merely an exemplary description of the scope of protection claimed by the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, and such changes should also fall within the scope of protection claimed by the present invention.

[0023] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0024] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all chemical reagents used in the embodiments of the present invention are obtained through conventional commercial means.

[0025] Example 1: Fabrication of a sports knee brace sensor; refer to Figure 1 and Figure 2 This invention provides a magnetic microcrack textile composite sensor, comprising a textile substrate layer 1, a magnetic coating layer 2, an induction coil layer 3, and a moisture-permeable and waterproof encapsulation film 4. The textile substrate layer 1 is a polyester knitted fabric. The magnetic coating layer 2 is coated on the textile substrate layer 1, and comprises ferrite nanoparticles and water-based polyurethane. The ferrite nanoparticles are manganese-zinc ferrite nanoparticles. The magnetic coating layer 2 has a mesh-like microcrack structure, a thickness of 200 μm, and a mesh-like microcrack density of 50-120 cracks / cm. The induction coil layer 3 is disposed on the magnetic coating layer 2, and is formed by liquid metal embroidery. The liquid metal is a gallium indium tin alloy, and the induction coil layer 3 is a spiral coil. The moisture-permeable and waterproof encapsulation film 4 covers the induction coil layer 3, and is an expanded polytetrafluoroethylene microporous membrane with a thickness of 20 μm.

[0026] Its preparation method includes the following steps: (1) Preparation of magnetic coating: Ferrite nanoparticles are mixed with aqueous polyurethane dispersion to form magnetic slurry, wherein the ferrite nanoparticles account for 60% by mass in the magnetic slurry, and the thickness of the wet film is 200 μm. Polyester knitted fabric (thickness 0.3 mm) is used as textile substrate layer 1, and the magnetic slurry is coated onto the textile substrate layer 1 by a blade coating process to form a wet film.

[0027] (2) Generate mesh microcracks: Fix the textile substrate layer 1 coated with wet film on the tension frame, apply a tension of 15N for pre-stretching, and then dry it under hot air at 120℃ for 10min to form mesh microcracks on the surface of the magnetic coating 2. The density of the mesh microcracks is 50 cracks / cm-120 cracks / cm.

[0028] (3) Preparation of induction coil layer: Using a digital embroidery machine, embroider 6 turns of spiral coil on the surface of the magnetic coating 2 with gallium indium tin alloy wire (diameter 100μm). The embroidery parameters are: needle speed 800rpm, bottom thread tension 3cN, thread width 0.3mm, and spacing 0.5mm to form induction coil layer 3.

[0029] (4) Encapsulation: A Gore® microporous membrane (20 μm thick) is covered on the induction coil layer 3 and hot-pressed under the conditions of 130°C, 0.5 MPa and 30 s to obtain a magnetic microcrack textile composite sensor.

[0030] The resulting sensor has an overall thickness of less than 0.5 mm and a bending stiffness of less than 0.1 cN / cm².

[0031] Sensitivity Test: The sensor was worn on the human knee joint, and its sensitivity was evaluated by detecting the change in inductance during knee flexion. Test results showed that when the flexion angle was 0.01°, the inductance change was 0.05nH, and the signal-to-noise ratio was greater than 20dB.

[0032] The magnetic microcrack textile composite sensor of this embodiment uses a textile substrate layer 1 as a support layer. A magnetic coating layer 2 is applied, and a pre-stretching-drying process is used to form a mesh-like microcrack. When the sensor is bent, the mesh-like microcracks deform, causing a change in magnetic permeability, thereby achieving highly sensitive bending detection. The density of the mesh-like microcracks is 50-120 cracks / cm. During bending, the opening and closing of the cracks causes a significant change in the magnetic reluctance of the magnetic circuit, making the sensor highly sensitive to minute deformations. The bending sensitivity can reach 0.01°, which is approximately 50 times higher than that of traditional magnetic crack sensors.

[0033] Durability test: The sensor was subjected to a washing machine test according to GB / T 8629 standard, and the change in crack density was measured after 100 washes. The test results showed that the change in crack density was less than 8%, and the sensor could still function normally.

[0034] In this embodiment, the magnetic microcrack textile composite sensor is encapsulated with a moisture-permeable and waterproof encapsulation film 4. The moisture-permeable and waterproof encapsulation film 4 is an expanded polytetrafluoroethylene microporous membrane. The encapsulation film has good waterproof and moisture-permeable properties, which can effectively protect the internal structure from water washing damage. At the same time, the water-based polyurethane in the magnetic coating 2 acts as a binder phase, forming a stable composite structure with ferrite nanoparticles. The mesh microcracks formed by the pre-stretching-drying process remain stable during repeated deformation, giving the sensor good water washing stability. After 100 washing machine washes, the crack density change is less than 8%, which is more than 10 times longer than the water washing life of traditional adhesive laminate structure sensors.

[0035] Breathability test: The moisture permeability of the sensor was tested according to GB / T 12704.1-2009 standard. The test results showed that the moisture permeability was greater than 2000g / m² / 24h.

[0036] The magnetic microcrack textile composite sensor in this embodiment is encapsulated with a moisture-permeable and waterproof encapsulation film 4. The moisture-permeable and waterproof encapsulation film 4 is an expanded polytetrafluoroethylene microporous membrane. The microporous membrane has a large number of micropores with a pore size of about 0.2μm, which allows water vapor molecules to pass through while blocking liquid water penetration. The moisture permeability is greater than 2000g / m² / 24h, which ensures the wearing comfort of the sensor and solves the problems of poor breathability and stuffiness when wearing traditional magnetic sensors.

[0037] Application Example 1: Motion monitoring application; The magnetic microcracked textile composite sensor prepared in Example 1 was sewn into the knee joint of a sports knee brace. The sensor detects changes in inductance during knee flexion to achieve real-time monitoring of movement posture. When the test subject performs exercises such as running, jumping, and squatting, the sensor can accurately identify different movement patterns and output stable electrical signals, meeting the sensing requirements for motion monitoring.

[0038] This application example uses the magnetic microcracked textile composite sensor for motion monitoring. The sensor's high sensitivity enables it to capture minute bending changes in the knee joint and output inductive signals in real time, achieving accurate monitoring of human movement posture. It has significant application value in fields such as intelligent sports equipment and rehabilitation training assessment.

[0039] Example 2: Fabrication of a gesture recognition glove sensor; refer to Figure 1 and Figure 2This invention provides a magnetic microcracked textile composite sensor, comprising a textile substrate layer 1, a magnetic coating layer 2, an induction coil layer 3, and a moisture-permeable and waterproof encapsulation film 4. The textile substrate layer 1 is a polyester nonwoven fabric. The magnetic coating layer 2 is coated on the textile substrate layer 1, and comprises ferrite nanoparticles and water-based polyurethane. The ferrite nanoparticles are manganese-zinc ferrite nanoparticles. The magnetic coating layer 2 has a mesh-like microcrack structure and a thickness of 150 μm. The induction coil layer 3 is disposed on the magnetic coating layer 2 and is formed by weaving conductive yarn, specifically silver-plated nylon yarn. The induction coil layer 3 is a planar inductor. The moisture-permeable and waterproof encapsulation film 4 covers the induction coil layer 3 and is a polyurethane microporous membrane with a thickness of 15 μm.

[0040] Its preparation method includes the following steps: (1) Preparation of magnetic coating: Ferrite nanoparticles are mixed with aqueous polyurethane dispersion to form magnetic slurry, wherein the ferrite nanoparticles account for 60% of the mass of the magnetic slurry. Polyester nonwoven fabric (80 g / m²) is used as textile substrate layer 1, and the magnetic slurry is coated onto the textile substrate layer 1 by a blade coating process to form a wet film with a thickness of 150 μm.

[0041] (2) Generate mesh microcracks: Fix the textile substrate layer 1 coated with wet film on the tension frame, apply a tension of 12N for pre-stretching, and then dry it under hot air at 110℃ for 12min to form mesh microcracks on the surface of the magnetic coating 2.

[0042] (3) Preparation of induction coil layer: Silver-plated nylon yarn (resistivity less than 0.1Ω / cm) is interwoven with polyester yarn to form a double-sided jacquard structure, and a planar inductor coil is formed in the lower layer, namely induction coil layer 3.

[0043] (4) Encapsulation: A polyurethane microporous membrane (15 μm thick) is covered on the induction coil layer 3 and hot-pressed under the conditions of temperature 120℃, pressure 0.4MPa and time 40s to obtain a magnetic microcrack textile composite sensor.

[0044] The magnetic microcrack textile composite sensor of this embodiment uses conductive yarn woven into an induction coil layer 3. The silver-plated nylon yarn and polyester yarn are interwoven into a double-sided jacquard structure, with a planar inductor coil formed on the lower layer. The weaving process is compatible with the textile process, allowing the coil structure to be integrated directly during the fabric forming process, which is beneficial for mass production. At the same time, the silver-plated nylon yarn has good conductivity and flexibility, and can withstand repeated bending of textiles, solving the problem of easy breakage of traditional etched copper coils. The preparation method of this embodiment uses coating, pre-stretching-drying, weaving, and hot-pressing encapsulation processes. All of these processes are compatible with existing textile equipment, enabling roll-to-roll production at a production speed of not less than 5m / min, and have good feasibility for mass production.

[0045] Application Example 2: Pose Recognition and Human-Computer Interaction Applications; The magnetic microcracked textile composite sensor prepared in Example 2 was sewn into the knuckles of a glove. The sensor achieves gesture recognition by detecting changes in inductance during finger bending. When the tester performs gestures such as clenching a fist, extending, or pinching, the sensor can accurately identify different gesture postures and output corresponding electrical signals, which can be used for human-computer interaction control of virtual reality devices.

[0046] This application example uses the magnetic microcracked textile composite sensor for posture recognition and human-computer interaction. The sensor's high sensitivity and fast response characteristics enable it to capture subtle finger movements in real time, output stable inductive signals, and achieve accurate gesture recognition. It has broad application prospects in human-computer interaction fields such as virtual reality interaction, intelligent prosthetic control, and remote operation.

[0047] Comparative Example 1: Sensor with a traditional adhesive laminate structure; Unlike Example 1, an adhesive was used to laminate and fix the ferrite film to the copper coil, without a pre-stretching-drying process. Test results showed that the sensor failed after 10 washing machine cycles, with an air permeability of 0 mm / s and a bending sensitivity of 0.5°.

[0048] This comparative example shows that traditional adhesive-laminated sensor structures, due to their use of brittle ferrite films and rigid copper coils, cannot withstand repeated bending and washing of textiles, and the adhesive lamination results in extremely poor breathability, failing to meet the comfort requirements of wearable devices.

[0049] Comparative Example 2: Sensor without pre-stretching process; Unlike Example 1, no pre-stretching was performed in step (2), and the material was directly dried in hot air at 120°C for 10 minutes. Test results showed that no mesh-like microcracks were formed on the surface of the magnetic coating 2, and the bending sensitivity of the sensor was only 0.3°.

[0050] This comparative example shows that without the pre-stretching-drying process, an effective network microcrack structure cannot be formed on the surface of the magnetic coating 2. The magnetic circuit reluctance of the sensor changes only slightly during bending, resulting in a significant decrease in bending sensitivity, which fails to meet the requirements for high-sensitivity sensing. This demonstrates the crucial role of the pre-stretching-drying process in forming an effective crack structure.

[0051] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.

Claims

1. A magnetic microcrack textile composite sensor, characterized in that, include: Textile substrate layer; A magnetic coating is applied to the textile substrate layer. The magnetic coating comprises ferrite nanoparticles and waterborne polyurethane, and the magnetic coating has a network of microcracks. An induction coil layer is disposed on the magnetic coating layer, and the induction coil layer is formed by liquid metal embroidery or by conductive yarn weaving; A moisture-permeable and waterproof encapsulation film is provided, which covers the induction coil layer.

2. The magnetic microcrack textile composite sensor according to claim 1, characterized in that, The textile substrate layer is a polyester knitted fabric or a nonwoven fabric, and the ferrite nanoparticles are manganese-zinc ferrite nanoparticles.

3. The magnetic microcrack textile composite sensor according to claim 1, characterized in that, The thickness of the magnetic coating is 50μm-300μm, and the density of the mesh microcracks is 50-120 cracks / cm.

4. The magnetic microcrack textile composite sensor according to claim 1, characterized in that, The liquid metal is a gallium indium tin alloy, the conductive yarn is silver-plated nylon yarn, and the induction coil layer is a spiral coil or a planar inductor coil.

5. The magnetic microcrack textile composite sensor according to claim 1, characterized in that, The moisture-permeable and waterproof encapsulation film is an expanded polytetrafluoroethylene microporous film or a polyurethane microporous film, and the thickness of the moisture-permeable and waterproof encapsulation film is not greater than 20 μm.

6. A method for preparing a magnetic microcrack textile composite sensor, characterized in that, Includes the following steps: Ferrite nanoparticles are mixed with an aqueous polyurethane dispersion to form a magnetic slurry, which is then coated onto a textile substrate layer to form a wet film. The textile substrate layer coated with a wet film is stretched under tension and then dried under heating conditions to form a network of microcracks on the surface of the magnetic coating. An induction coil layer is formed on the surface of the magnetic coating by liquid metal embroidery or conductive yarn weaving; A moisture-permeable and waterproof encapsulation film is applied to the induction coil layer, and then encapsulated using a hot-pressing process to obtain a magnetic microcrack textile composite sensor.

7. The preparation method according to claim 6, characterized in that, The ferrite nanoparticles account for 60% of the mass of the magnetic slurry, and the thickness of the wet film is 150μm-250μm.

8. The preparation method according to claim 6, characterized in that, The tension is 10N-20N, the heating temperature is 100℃-150℃, and the drying time is 8min-15min.

9. The preparation method according to claim 6, characterized in that, The liquid metal embroidery is performed using a digital embroidery machine. The embroidery parameters are: needle speed 800 rpm, bobbin tension 3 cN, number of coil turns 6, line width 0.3 mm, and spacing 0.5 mm. The hot pressing process conditions are: temperature 120℃-140℃, pressure 0.4MPa-0.6MPa, and time 20s-40s.

10. An application of the magnetic microcrack textile composite sensor according to any one of claims 1-5, characterized in that, The magnetic microcrack textile composite sensor is used for motion monitoring, posture recognition, or human-computer interaction.

Citation Information

Patent Citations

  • Bidirectional bending sensor based on crack gap magnetic resistance modulation

    CN117128848A